A distinct look at a transcendental phenomenon: the grounded theory model of leader humour - Mohammad Gholami; Fariborz Rahimnia; Gholamreza Malekzadeh; Alireza Khorakian (BMC Psychology)
Abstract Background Humour is an essential quality and key factor in communication, particularly in leadership. This study explores leader humour within university departments to design a comprehensive model using grounded theory. The study also examines the effects and dynamics of humour in leadership and its influence on followers. Methods This qualitative study employed Glaser’s 6 C family approach. Data were collected from 18 Iranian university professors, selected via purposive sampling until theoretical saturation was reached. Semi-structured interviews were conducted, and data were analysed using MAXQDA2020 software to facilitate the coding process. Results The axial category was named ‘leader humorous behaviour’ and the main attributes of humour were ‘benign violation’ and ‘moderation’. This study highlights the importance of moderation in humorous behaviour (frequency and repetition) as an important attribute of leader humour alongside benign violation, which can have negative and unwanted outcomes for both leader and followers despite positive and constructive content. The final model identifies a sense of humour as the central cause and organisational factors as correlated causes. It also identifies the mediators, moderators, context, and consequences of leader humorous behaviour. Sense of humour is found to be the most important factor in followers’ perception and interpretation of leader humour. Conclusions Leader humour can have positive ethical implications in organisations, thus enhancing relationships and communication when employed appropriately. The findings suggest that positive outcomes of leader humour over time foster greater expression and mitigate misunderstandings. This study offers a foundational understanding of leader humorous behaviour and its potential positive outcomes in organisational settings.